2010
DOI: 10.1111/j.1528-1167.2010.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability, and safety of rapid initiation of topiramate versus phenytoin in patients with new‐onset epilepsy: A randomized double‐blind clinical trial

Abstract: SUMMARYPurpose: To evaluate topiramate (TPM) and phenytoin (PHT) monotherapy following rapid oral initiation in newonset epilepsy. Methods: Randomized, double-blind, 28-day trial of TPM (100 mg/day beginning on day 1) versus PHT (1,000 mg on day 1 followed by 300 mg/day maintenance dosing) in 261 patients with new-onset epilepsy. The primary end point was time to seizure, and the primary objective was to establish noninferiority of TPM to PHT in the risk of seizure. Results: At day 28, the estimated seizure-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…6063 The prevalence of AEs with phenytoin use has been shown to be dose-related and independent of concomitantly administered medications. 64 In one study, 86% of patients with toxicity had phenytoin-free levels >2 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…6063 The prevalence of AEs with phenytoin use has been shown to be dose-related and independent of concomitantly administered medications. 64 In one study, 86% of patients with toxicity had phenytoin-free levels >2 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…30 For example a study of patients with new-onset epilepsy found initial AED monotherapy with either phenytoin or topiramate was associated with AEs leading to AED discontinuation in only 7% to 13% of patients. 32 Another in a mixed group of patients with epilepsy initially treated with AEDs found that AEs were no more likely to occur than in untreated controls and proposed that this was because the drugs were typically started as monotherapy and at low doses. 31 Conclusion.…”
Section: 29-32mentioning
confidence: 99%
“…30 For example, a study of patients with new-onset epilepsy found that initial AED monotherapy with either phenytoin or topiramate was associated with AEs leading to AED discontinuation in only 7% to 13% of patients. 32 Another study in a mixed group of patients with epilepsy initially treated with AEDs found that AEs were no more likely to occur than in untreated controls and proposed that this was because the drugs were typically started as monotherapy and at low doses.…”
mentioning
confidence: 99%